2022
DOI: 10.1021/acs.langmuir.2c00982
|View full text |Cite
|
Sign up to set email alerts
|

On the Coupled Thermal and Hydrodynamic Interaction of Adjacently Located Vapor Bubbles on Highly Wetting Surfaces

Abstract: Spatio-temporally resolved IR measurements coupled with high-speed videography have been made to propose the regime map of the interaction between two adjacently located vapor bubbles on highwettability surfaces. The modes of interaction (thermal and/or hydrodynamic) have been studied as a function of distance between the two nucleation sites under saturated nucleate pool boiling conditions with water as the working fluid, and their effects on the wall heat-transfer rates have been quantified. Based on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They suggested that hydrodynamic interaction takes place when 1.5 < S / D < 2, and hydrodynamic and thermal interaction come into play when 1.5 < S / D < 2, while hydrodynamic, thermal and coalescence take place when S / D < 1.5. Recently, Kangude & Srivastava (2022) have also classified the type of bubble interactions based on the observations made through simultaneous application of high-speed videography and IR thermography under pool boiling conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that hydrodynamic interaction takes place when 1.5 < S / D < 2, and hydrodynamic and thermal interaction come into play when 1.5 < S / D < 2, while hydrodynamic, thermal and coalescence take place when S / D < 1.5. Recently, Kangude & Srivastava (2022) have also classified the type of bubble interactions based on the observations made through simultaneous application of high-speed videography and IR thermography under pool boiling conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the available literature also shows that while the hydrodynamic interaction of bubbles is appreciated in boiling conditions, the phenomenon of depletion of the microlayer has not yet been given its due attention. This becomes even more important because depletion of the microlayer has a strong thermal impact as well (Kangude & Srivastava 2022). Even separating the two effects is very challenging.…”
Section: Introductionmentioning
confidence: 99%